ICAM-1 and SRD5A1 gene polymorphisms in symptomatic peripheral artery disease. (June 2014) - Barresi, Vincenza; Signorelli, Salvatore S; Musso, Nicolò; Anzaldi, Massimiliano; Fiore, Valerio; Alberghina, Mario; Condorelli, Daniele Filippo
The genotype distribution of two gene polymorphisms, previously associated with peripheral artery disease (PAD), has been evaluated in a population of diabetic (DPAD) and non-diabetic (NDPAD) patients affected by symptomatic PAD (stages II–IV). A decreased frequency of the AA genotype of rs5498 (ICAM-1) was observed in the PAD subjects compared to controls but this result did not reach statistical significance ( p =0.06 by chi-squared test). On the contrary, a significant increase in the frequency of the GG homozygous genotype of rs248793 (SRD5A1) was observed in the PAD patient group in comparison to controls ( p =0.01). These data confirm that the GG genotype of rs248793 in the SRD5A1 gene is significantly associated with symptomatic PAD and show a trend towards a stronger association with the non-diabetic status.